2015
DOI: 10.17795/jhealthscope-25467
|View full text |Cite
|
Sign up to set email alerts
|

A Fairly Comprehensive Survey of Chronic Pain in Iranian Population: Prevalence, Risk Factors, and Impact on Daily Life

Abstract: Background: Chronic pain has been estimated to affect between 2% -40% of the adult population and its prevalence is increasing. Objectives: This study aimed to provide epidemiological data of chronic pain and associated factors in Tehran, capital of Iran. Patients and Method:We analyzed the data of 23457 people, from the Urban HEART-2 (health equity assessment and response tool) study in Tehran, collected in October 2011, and determined the association between any type of chronic pain and other variables using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It was similar to, or even lesser than that reported among general population or other occupational groups (such as health care workers) in Iran. 3,25,26 This could, in principle, be due to one or more of the following reasons: (1) as previously described, the majority of these workers were young males seeking promotions in their first years on the job. Therefore, having a mean experience of <7 years, workers studied in our study expectedly had a lower mean age than those reported in populationbased studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was similar to, or even lesser than that reported among general population or other occupational groups (such as health care workers) in Iran. 3,25,26 This could, in principle, be due to one or more of the following reasons: (1) as previously described, the majority of these workers were young males seeking promotions in their first years on the job. Therefore, having a mean experience of <7 years, workers studied in our study expectedly had a lower mean age than those reported in populationbased studies.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have found a higher prevalence of chronic pain amongst women, 1,3 most studies have found no sex differences. 25,33 Defrin, et al, have discussed that the difference in response to pain is complex and may be affected by culture. 35 Similar to other published studies, 1,36 the most frequent marital status in workers with chronic pain was divorced/widowed.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing age, the work ability of workers in physically demanding jobs reduces more than the workers in mentally demanding jobs (7). Because the increase in the age leads to the chronic low back pain and knee pain in these people (24). As a result, the necessary measures should be taken to reform their tasks.…”
Section: (N = 15)mentioning
confidence: 99%
“…This pain may directly and/or indirectly affect the structure and function of nerve cells [3,4]. The prevalence of Iranians suffering from neuropathic pain is calculated between 2%-40% of adults and is it is increasing over time [5]. About 20% (50 million) of the American population suffers from neuropathic pain, highlighting the importance of this disease [6].…”
Section: Introductionmentioning
confidence: 99%